The effects of exercise intensity on visual choise reaction times performances - Sanchez, X.; Barnes, K. J.; Jones, M. A. (Journal of Sports Sciences, 2005)
Ziel der Studie war die Untersuchung verschiedener Belastungsintensitäten auf die Leistung der Visual Choise Reaction Time.